Sauropodomorph dinosaur trackways from the Fleming Fjord Formation of East Greenland: evidence for Late Triassic sauropods - Lallensack, Jens N.; Klein, Hendrik; Milàn, Jesper; Wings, Oliver; Mateus, Octávio; Clemmensen, Lars B. (Acta Palaeontologica Polonica, 2017)
The Late Triassic (Norian–early Rhaetian) Fleming Fjord Formation of central East Greenland preserves a diverse fossil fauna, including both body and trace fossils. Trackways of large quadrupedal archosaurs, although already reported in 1994 and mentioned in subsequent publications, are here described and figured in detail for the first time, based on photogrammetric data collected during fieldwork in 2012. Two trackways can be referred to Eosauropus, while a third, bipedal trackway may be referred to Evazoum, both of which have been considered to represent sauropodomorph dinosaur tracks. Both the Evazoum and the Eosauropus trackways are distinctly larger than other trackways referred to the respective ichnogenera. The trackmaker of the best preserved Eosauropus trackway is constrained using a synapomorphy-based approach. The quadrupedal posture, the entaxonic pes structure, and five weight-bearing digits indicate a derived sauropodiform trackmaker. Other features exhibited by the tracks, including the semi-digitigrade pes and the laterally deflected unguals, are commonly considered synapomorphies of more exclusive clades within Sauropoda. The present trackway documents an early acquisition of a eusauropod-like pes anatomy while retaining a well-developed claw on pedal digit IV, which is reduced in eusauropods. Although unequivocal evidence for sauropod dinosaurs is no older than the Early Jurassic, the present trackway provides evidence for a possible Triassic origin of the group. publishersversion published